If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 = 4x + -3 Reorder the terms: 2 + 6x = 4x + -3 Reorder the terms: 2 + 6x = -3 + 4x Solving 2 + 6x = -3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2 + 6x + -4x = -3 + 4x + -4x Combine like terms: 6x + -4x = 2x 2 + 2x = -3 + 4x + -4x Combine like terms: 4x + -4x = 0 2 + 2x = -3 + 0 2 + 2x = -3 Add '-2' to each side of the equation. 2 + -2 + 2x = -3 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = -3 + -2 2x = -3 + -2 Combine like terms: -3 + -2 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5
| a*5-60=a | | 1.5(x-1)=1 | | 10+15x=5y | | (X+4)(x-3)=(x+1)(x-2) | | 7+10x-x+-x=0 | | 5(8-2x)=20 | | 17*2= | | 4(1/3+2)=28 | | 4(n/3+2)=28 | | 7+10x-x+-1=0 | | 2.9y=y+3.2+0.2 | | (-8/x)=(-18/x-5) | | (-1-4)x2/-1-4 | | 3+14*n=31 | | n/7=49 | | 7y=-3.9 | | 3.2x-7.4=7.8+3.6 | | x/5-1=12 | | -20x=4 | | 2.6q=1.872 | | 1.3b-0.03=-9 | | 3x=5y+3 | | 5x-26=36 | | 12=2b+3.2 | | -12=-8z+2 | | y=7-4*-2 | | 3/8r=-6 | | a^2-8+12=0 | | (X+3)(x+3)=-4 | | 181x+91x-23x= | | -2=-3(2q-1) | | -32t=16t^2 |